Comparison of Dorsal-to-Ventral Ratios of the Cervical Paraspinal Musculature in French Bulldogs With and Without Cervical Intervertebral Disk Disease and Two Other Breeds Based on CT Scan Measurements - Hart, Julia; Rupp, Stefan; Hartmann, Katinka; Fischer, Carolin; Düver, Pia; Forterre, Franck (Frontiers in Veterinary Science, 2021)
Objective: To objectively assess the cervical paraspinal musculature of French Bulldogs (FBs) using computed tomography (CT) scan-based measurements, outline differences in other breeds published in the literature, and investigate the potential influence of its cervical paraspinal musculature on predisposed sites for intervertebral disk disease. Animals: Thirty FBs that underwent CT scans of the cervical spine from the skull to C7/T1 were enrolled. Fifteen dogs were patients suffering from intervertebral disk herniation (IVDH group), and 15 dogs underwent CT scans due to brachycephalic obstructive airway syndrome (BOAS group). Methods: At the level of each cervical intervertebral disk from C2/C3 to C7/T1, measurements were performed and statistically analyzed. On the sagittal CT scan reconstruction, the height ratio of the dorsal to ventral paraspinal musculature and the angle of the disk axis to vertebral body length were assessed. On the transverse plane, the area ratio of the dorsal and ventral paraspinal musculature and the ratio of force moments were determined at each intervertebral disk level. Finally, ratios were compared to the values of Labrador Retrievers and Dachshunds published by Hartmann et al. 2020. Results: Comparing the two FB groups, one significant difference was detected in the mean height ratio of the dorsal to ventral paraspinal musculature at the level of C5/C6 (P = 0.0092) and C6/C7 (P = 0.0076), with IVDH FBs having the more prominent dorsal paraspinal musculature. At the level of C3/C4, a significantly less prominent dorsal paraspinal musculature in FBs than in Dachshunds (P = 0.0058) and a significantly steeper disk to vertebral body angulation were observed (P = 0.0005). Conclusion: Although some incidental differences were found, most parameters did not significantly differ between the BOAS and IVDH FBs. Significant conformational differences in the cervical paraspinal musculature and disk to vertebral body length angulation were found between FBs and two other breeds (chondrodystrophic and non-chondrodystrophic). This study’s findings suggest that the paraspinal musculature is an additional biomechanical influencing factor on the preferential sites of IVDH in the cervical spine and that other major factors exist in IVDH development, especially in FBs.